2023
DOI: 10.1097/nnr.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Listening Visits for Mothers of Hospitalized Newborns

Abstract: BackgroundEmotional distress is frequently experienced by mothers whose newborns are hospitalized in a neonatal intensive care unit (NICU). Among these women, there is a critical need for emotional support conveniently delivered at the newborn’s point of care by a trusted and medically knowledgeable professional: a NICU nurse. One promising way to enhance in situ delivery of emotional care is to have a NICU nurse provide Listening Visits (LVs), a brief support intervention developed expressly for delivery by n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…This multiple case study was a secondary analysis of qualitative data collected during the RCT of Listening Visits for depressed mothers of hospitalized infants (Segre et al, 2023). We used the RCT dataset to answer a different research question that had been examined in the primary study, a research strategy recommended by Beck (2019).…”
Section: Study Design and Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This multiple case study was a secondary analysis of qualitative data collected during the RCT of Listening Visits for depressed mothers of hospitalized infants (Segre et al, 2023). We used the RCT dataset to answer a different research question that had been examined in the primary study, a research strategy recommended by Beck (2019).…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Although embedded design examines cases at more than one level, a holistic design focuses on cases' global nature and aims to understand phenomena in real-world situation, a colla borative partnership, and em powering the mother. Clinical trial evaluations of Listening Visits in the NICU setting found promising outcomes (Segre et al, 2013;Segre et al, 2022;Segre et al, 2023); and that NICU mothers value this approach (Segre et al, 2016).…”
Section: Case Study Designmentioning
confidence: 99%
See 3 more Smart Citations